Steep Balmer Decrement in Weak AGNs May Not Be Caused by Dust Extinction: Clues from Low-luminosity AGNs and Changing-look AGNs - Jiancheng Wu; Qingwen Wu; Hanrui Xue; Weihua Lei; Bing Lyu (The Astrophysical Journal, 2023)
The hydrogen Balmer decrement (e.g., H α /H β ) is widely adopted as an indicator of the internal reddening of active galactic nuclei (AGNs). This is challenged by some low-luminosity AGNs and changing-look AGNs (CLAGNs), which have steep Balmer decrement but without strong evidence for absorption. We compile a sample of normal AGNs and CLAGNs with a wider distribution of bolometric Eddington ratio ( λ _Edd = L _bol / L _Edd ) and find a strong negative correlation between H α /H β and λ _Edd , which suggests that the Balmer decrement is also accretion-rate dependent. We further explore the Balmer decrement based on the photoionization model using the Cloudy code by considering spectral energy distribution from the accretion disk with different accretion rates (e.g., disk/corona and truncated disk at high and low Eddington ratios, respectively). Both the standard disk and truncated disk predict a negative correlation of H α /H β – λ _Edd , where the relation is steeper in the case of the truncated disk. The negative correlations are also explored in two single CLAGNs. The measured negative correlation of H α /H β – λ _Edd is mainly caused by the lower responsivity $(dlogL_{line}/dlogL_{cont})$ in H α relative to that in H β due to the larger optical depth in the former. We propose that the steep Balmer decrements in low Eddington ratio AGNs (e.g., some Seyferts 1.5–1.9 and CLAGNs) are not simply caused by absorption but mainly caused by the relatively low flux of ionizing photons.